To solve the equation \( 5x - 12 - 6x = -10x + 7 - 1 \), we can follow these steps:
-
Combine like terms on both sides:
On the left side: \[ 5x - 6x - 12 = -x - 12 \]
On the right side: \[ -10x + 7 - 1 = -10x + 6 \]
Now the equation looks like: \[ -x - 12 = -10x + 6 \]
-
Add \( 10x \) to both sides: \[ -x + 10x - 12 = 6 \] This simplifies to: \[ 9x - 12 = 6 \]
-
Add 12 to both sides: \[ 9x - 12 + 12 = 6 + 12 \] This simplifies to: \[ 9x = 18 \]
-
Divide by 9: \[ x = \frac{18}{9} \] This simplifies to: \[ x = 2 \]
So, the final answer is \( x = 2 \).